DRAMATIC WORKS AND THE SAD CONCEPT OF SPEECH (Archive of Conferences, 2021)
The article discusses the concept of sadness of speech, which is relevant for today's linguistics, and its appearance in dramatic speech. The examples are analyzed within the grief type of speech